A Study on Immigration Cooperation Between Indonesia and Taiwan - Seno Setyo Pujonggo; Mila Rosmaya; Gunawan Ari Nursanto; Virra Wirdhiningsih (Jurnal Ilmiah Kajian Keimigrasian, 2022)
Indonesia adheres to the One China Policy in its view of the relationship between China and Taiwan so that Indonesia doesn’t have diplomatic relation with Taiwan. However, this did not stop the cooperation between Indonesia and Taiwan due to the interdependence of interests between the two countries. Starting in the fields of trade and economy, followed by other fields such as agriculture and education, the movement of people between the two parties is increasing. This makes them feel the important need to also work together in meeting the needs of their citizens and it is an obligation for the government to provide facilities and protection for them abroad. By using the concept of international cooperation, this paper tries to discuss the cooperation in the field of immigration in facilitating the interests of the two countries in the form of a strategic and sectoral non-governmental organization of IETO and TETO. The agreement of immigration cooperation results in the matters that must be provided by the state to protect their respective citizens by technical frameworks and the method about how to achieve these goals in the implementation level. The agreement itself remains valid and the subject of international law bond between the two parties.